2021
DOI: 10.3390/universe7100372
|View full text |Cite
|
Sign up to set email alerts
|

A New Sample of Gamma-Ray Emitting Jetted Active Galactic Nuclei—Preliminary Results

Abstract: We are compiling a new list of gamma-ray jetted active galactic nuclei (AGN), starting from the fourth catalog of point sources of the Fermi Large Area Telescope (LAT). Our aim is to prepare a list of jetted AGN with known redshifts and classifications to be used to calibrate jet power. We searched in the available literature for all the published optical spectra and multiwavelength studies useful to characterize the sources. We found new, missed, or even forgotten information leading to a substantial change i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…We carefully checked the sample of Paliya et al ( 2021) and compared it with the source classification of Abdollahi et al ( 2020 ) and Foschini et al ( 2021 ), and found that 17 γ -ray narrow-line Seyfert 1 galaxies ( γ NLS1s) were included in the sample of Paliya et al ( 2021 ). We only consider these sources with 1.4 GHz radio flux from the NED.…”
Section: Jet Kinetic Powermentioning
confidence: 99%
“…We carefully checked the sample of Paliya et al ( 2021) and compared it with the source classification of Abdollahi et al ( 2020 ) and Foschini et al ( 2021 ), and found that 17 γ -ray narrow-line Seyfert 1 galaxies ( γ NLS1s) were included in the sample of Paliya et al ( 2021 ). We only consider these sources with 1.4 GHz radio flux from the NED.…”
Section: Jet Kinetic Powermentioning
confidence: 99%
“…Despite multiple observations suggesting that NLS1s have low-mass BHs, several NLS1s have been detected at γ-rays (Abdo et al 2009a,b;Paliya et al 2018;Foschini et al 2021), confirming the presence of powerful relativistic jets in them. This goes against the fact that, until recently, it was believed that powerful jets could only be harboured in elliptical galaxies, hosting the most massive supermassive BHs (Urry & Padovani 1995;Franceschini et al 1998;Kotilainen et al 2005).…”
Section: Introductionmentioning
confidence: 97%
“…We also found many reports on sources displaying strong changes in the optical spectra, from line-dominated spectra to featureless ones (changing-look AGN). We also found that many of the commonly adopted redshifts were not correct, because of mere transcription errors from the paper to the database, old and outdated information, lower limits taken as measurements, and many other problems (Foschini et al, 2021). This is really a time-consuming work, but nonetheless it must be done, otherwise, we will continue to study and to draw fake conclusions on strongly biased samples.…”
Section: Final Remarksmentioning
confidence: 96%